THE ROLE OF SHARIA COOPERATIVE MITRA INSAN MANDIRI (MIM) IN THE POST-PANDEMIC COMMUNITY ECONOMIC RECOVERY - Mulyadi, Sandi; Suryanto, Asep; Mulyati, Sri (Jurnal Al-Iqtishad, 2023)
The role of the MIM sharia cooperative (Mitra Insan Mandiri) in carrying out operational activities, one of which can be seen from the level of public trust in the MIM sharia cooperative, when the rapid spread of the coronavirus resulted in economic problems that occurred in Indonesia, including the Tasikmalaya area. Tasikmalaya is an area affected by the economy and social community, not least the impact on Islamic financial institutions including sharia cooperatives. This study was conducted to analyze the role and growth of sharia cooperatives during the coronavirus pandemic in MIM sharia cooperatives. This research is a descriptive study using a quantitative approach, this research is focused on a SWOT analysis of internal and external factors such as opportunities, threats, strengths, and weaknesses. The study used observational techniques in the form of observing data related to the coronavirus. The results obtained indicate that with the coronavirus pandemic, MIM's sharia cooperative financial reports have an impact on financing achievement, revenue achievement, and operating profit achievement